(untitled) (Experimental biology, 2023)
To date, pathogenic strains of the influenza A virus have caused several dangerous pandemics and caused high mortality. Viral diseases cause irreversible pathology, which leads to a significant decrease in productivity and death of the infected bird. The only way to protect birds from the avian influenza virus is to keep birds in isolation and develop immunity in birds to the pathogen through vaccines. However, despite the above possibilities of protection against the above-mentioned viral pathogens, the epizootic situation among birds in many countries, including the Republic of Kazakhstan, remains tense. There are many publications on the development of test systems, but the variability of the AIV genome and its susceptibility to mutations creates serious problems in laboratory evaluation. In this regard, the development of effective domestic methods for the rapid diagnosis of avian influenza, such as PCR test systems, is relevant. Thus, this is the only express method necessary to further strengthen the complex of veterinary-sanitary and special veterinary measures to prevent the spread of infection in the country. For this purpose, more than 30 samples were selected in the North Kazakhstan region for the selection and design of specific oligonucleotide primers for the detection of AIV.